Hemoglobin Variant Profiles among Brazilian Quilombola Communities. (4th March 2017) - Santiago, Rayra P.; Oliveira, Rodrigo M.; Soares, Leonardo F.; Figueiredo, Camylla V. B.; Silva, Denise Oliveira; Hurtado-Guerrero, Ana F.; Fiuza, Luciana M.; Guarda, Caroline C.; Adorno, Elisângela V.; Barbosa, Cynara G.; Gonçalves, Marilda S.
Abstract: Brazilian Quilombolas are communities composed of African-derived populations that have their territories guaranteed by the Brazilian Constitution. The present study investigated the hemoglobin (Hb) variants among these population groups. This study was conducted in a total of 2843 individuals of Brazilian Quilombola communities of the Bahia, Pará, and Piauí states. All the participants had their Hb profiles evaluated. The Hb S ( HBB : c.20A>T) variant was described in all the studied localities. However, the individuals in Bahia State had the highest frequency of the Hb C ( HBB : c.19G>A) variant; individuals from Piauí State had a higher frequency of the Hb D-Punjab ( HBB : c.364G>C) variant compared to the other states, and individuals from Pará State only carried the Hb S variant. The present study revealed a specific distribution of Hb variants that could represent different waves of African influence in these Brazilian populations.